2011
DOI: 10.1371/journal.pgen.1002248
|View full text |Cite
|
Sign up to set email alerts
|

Tsx Produces a Long Noncoding RNA and Has General Functions in the Germline, Stem Cells, and Brain

Abstract: The Tsx gene resides at the X-inactivation center and is thought to encode a protein expressed in testis, but its function has remained mysterious. Given its proximity to noncoding genes that regulate X-inactivation, here we characterize Tsx and determine its function in mice. We find that Tsx is actually noncoding and the long transcript is expressed robustly in meiotic germ cells, embryonic stem cells, and brain. Targeted deletion of Tsx generates viable offspring and X-inactivation is only mildly affected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 41 publications
(61 reference statements)
5
114
0
Order By: Relevance
“…The distal recombination breakpoint for RX2-derived male 830m (and 3695m) lies between DXPas28 and Exon 4 of Tsx (Table S1 and Table S2); therefore, Xite can be excluded but Tsx may still be part of this Xce candidate region. This is interesting because Tsx is reported to affect Tsix expression (Anguera et al 2011). In addition, the expression and transgenic analysis of the noncoding gene Linx, which is within the 830m X chromosome distal recombination breakpoint, suggests that Linx expression affects XCI choice and therefore Linx may also be a candidate for the Xce QTL ( Figure 5A) (Nora et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…The distal recombination breakpoint for RX2-derived male 830m (and 3695m) lies between DXPas28 and Exon 4 of Tsx (Table S1 and Table S2); therefore, Xite can be excluded but Tsx may still be part of this Xce candidate region. This is interesting because Tsx is reported to affect Tsix expression (Anguera et al 2011). In addition, the expression and transgenic analysis of the noncoding gene Linx, which is within the 830m X chromosome distal recombination breakpoint, suggests that Linx expression affects XCI choice and therefore Linx may also be a candidate for the Xce QTL ( Figure 5A) (Nora et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Testis-specific X-linked (Tsx) was thought to be a proteincoding gene, but has recently been shown to be a lncRNA (Anguera et al 2011). The same group also found that Tsx is specifically expressed in pachytene spermatocytes, but not in spermatogonia or round spermatids, suggesting a regulatory role in germline meiotic division.…”
Section: Testis-specific X-linked (Tsx)mentioning
confidence: 99%
“…Plasticity lncRNAs are also implicated in modulating synapse formation and function. In particular, nuclear enriched abundant transcript 2 (NEAT2)/metastasis-associated lung adenocarcinoma transcript 1, brain cytoplasmic RNA 1, and testes-specific Xlinked are all lincRNAs that regulate synaptogenesis, local protein synthesis at the synapse, and fear-conditioning and short-term hippocampal memory consolidation, respectively [40][41][42]. Other lncRNAs are transcribed from genomic loci encompassing protein-coding genes involved in synapse development and functioning.…”
Section: Brain Developmentmentioning
confidence: 99%